Uprawnienia normotwórcze Międzynarodowej Organizacji Morskiej - Gilas, Janusz (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
International Maritime Organization (IMO) is equipped with considerable legislative competence consisting in passing recommendations and international conventions. Conventions become binding after their ratification, and recommendations — after their implementation. In the case of Poland, when out of 635 decrees of IMO we are bound only by 4, with 1 of them in an outdated version, a solution might be to leave the question of ratification of international codes, codes, indications and handbooks to the Minister of Transport, Navigation and Communication, while the ratification of other decrees might be left to the director of Polish Register of Ships, to directors of Maritime Offices or to directors of sea-ports or other maritime enterprises. A problem in Poland is how to acquaint all interested persons with the contents of those decrees. According to the requirements of the legislative technique, ordinances of the Minister of Transport would have to be published in one of the promulgation organs (Dziennik Ustaw, Monitor Polski, Dziennik Urzędowy). Because of the great number of decrees which, in order to create safe conditions of navigation, should be ratified, it seems necessary to use the method of publishing a comprehensive index of decrees, indicating the institution which collects the texts. In all other cases it seems possible to publish and collect the texts in the IMO Centre at the Polish Register of Ships in Gdańsk. IMO conventions do not guarantee a full uniformization of maritime law on a world scale. Summing up, one may say that the conventions are not self- -executing agreements and that with respect to ratifying annexes a principle of individual opting-out has not been adopted. For these reasons IMO international maritime law cannot be identified with domestic maritime law. In order to distinguish the former from the latter the term „international maritime legislation" should be used.
Legislative competence of International Maritime Organization